2019
DOI: 10.1016/j.ejrad.2019.108696
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging in peritoneal carcinomatosis from suspected ovarian cancer: Diagnostic performance in correlation with surgical findings

Abstract: INTRODUCTION: Ovarian Cancer (OC) is the first death cause by gynaecological cancer in developed countries and the third cause of gynaecological cancer in the world. Detecting irresectable disease is crucial to select surgical candidates and Peritoneal Carcinomatosis (PC) depiction helps to get a complete debulking without residual disease >1cm, the best prognostic predictor in advanced OC. CT is the elective technique for abdominal imaging, although its accuracy for PC in OC and cytoreduction success predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This study found that MRI was useful in determining the PCI and that it may have a role in predicting successful cytoreduction, but this study was limited with only 25 participants [76]. A second study had similar findings in a slightly larger sample of 50 patients, but further research is needed prior to expanding the role of MRI in the diagnosis and management of ovarian cancer [77].…”
Section: Preoperative Imagingmentioning
confidence: 91%
“…This study found that MRI was useful in determining the PCI and that it may have a role in predicting successful cytoreduction, but this study was limited with only 25 participants [76]. A second study had similar findings in a slightly larger sample of 50 patients, but further research is needed prior to expanding the role of MRI in the diagnosis and management of ovarian cancer [77].…”
Section: Preoperative Imagingmentioning
confidence: 91%
“…MCR [ 10 ] and objective evaluation index KI [ 11 ] are adopted to analyze the accuracy of algorithm segmentation. Among them, the calculation method of MCR is MCR=( M / T ), where M represents the number of misclassified pixels, and N represents the total number of pixels in the image.…”
Section: Methodsmentioning
confidence: 99%
“…Both MRI and PET/CT have been shown to be useful in the preoperative staging of peritoneal metastases. In particular, diffusion MRI has been shown to provide better diagnostic performance than CT or PET/CT, with good correlation with surgical PCI [56,57]. However, both imaging modalities have limitations.…”
Section: Pet/mrmentioning
confidence: 99%